2018
DOI: 10.1098/rsob.180158
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase NlHDAC1 regulates both female and male fertility in the brown planthopper,Nilaparvata lugens

Abstract: Histone acetylation is a specific type of chromatin modification that serves as a key regulatory mechanism for many cellular processes in mammals. However, little is known about its biological function in invertebrates. Here, we identified 12 members of histone deacetylases (NlHDACs) in the brown planthopper (BPH), Nilaparvata lugens. RNAi-mediated silencing assay showed that NlHdac1, NlHdac3 and NlHdac4 played critical roles in female fertility via regulating ovary maturation or ovipositor development. Silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 74 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…In contrast, in solitary insects such as the pea aphid, the inhibition of histone acetylation and deacetylation affects development, fertility, and longevity (Kirfel, Kessel, Skaljac, Seip, & Vilcinskas, 2020). In fact, fertility appears to be regulated by this epigenetic mark in various taxonomic groups, which includes other insects such as the planthopper Nilaparvata lugens (Zhang et al, 2018), but also mammals including mice (Ma, Pan, Montgomery, Olson, & Schultz, 2012) and men (Wang, Gao, Li, & Liu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in solitary insects such as the pea aphid, the inhibition of histone acetylation and deacetylation affects development, fertility, and longevity (Kirfel, Kessel, Skaljac, Seip, & Vilcinskas, 2020). In fact, fertility appears to be regulated by this epigenetic mark in various taxonomic groups, which includes other insects such as the planthopper Nilaparvata lugens (Zhang et al, 2018), but also mammals including mice (Ma, Pan, Montgomery, Olson, & Schultz, 2012) and men (Wang, Gao, Li, & Liu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Former studies have showed that silencing of the TOR gene in BPHs leads to unmatured eggs (Lu et al, 2016). The TOR nutritional signaling pathway and juvenile hormone (JH) regulation of vitellogenesis has been known for a long time (Zhai et al, 2015;Zhuo et al, 2017;Roy et al, 2018;Zhang et al, 2019). The possible involvement of NlTMC3 in TOR or JH signaling in N. lugens females needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disturbances such as ketone body β-hydroxybutyrate (BOHB) has been demonstrated as an inhibitor of H3K27 and hyperacetylation [129]. Histone deacetylases (NIHDAC) play an important role in female fertility by regulating ovary maturation or ovipositor development [130]. Loss of histone acetylation inhibits chromatin accessibility and nucleosome eviction during spermiogenesis which leads to poor fertility in males [131].…”
Section: Dna Methylation and Histone Acetylationmentioning
confidence: 99%